Iron concentration in breast milk normalised within one week of a single high_dose infusion of iron isomaltoside in randomised controlled trial. (22nd December 2016) - Holm, Charlotte; Thomsen, Lars Lykke; Norgaard, Astrid; Markova, Veronika; Michaelsen, Kim F.; Langhoff_Roos, Jens
Abstract: Aim: We compared the iron concentration in breast milk after a single high dose of intravenous iron isomaltoside or daily oral iron for postpartum haemorrhage. Methods: In this randomised controlled trial, the women were allocated a single dose of intravenous 1200 mg iron isomaltoside or oral iron at a mean daily dose of 70.5 mg. We included 65 women with sufficient breast milk three days after inclusion _ 30 from the intravenous iron group and 35 from the oral iron group _ and collected breast milk and maternal blood samples three days and one week after allocation. Results: The mean (_SD) iron concentration in breast milk in the intravenous and oral groups was 0.72 _ 0.27 and 0.40 _ 0.18 mg/L at three days (p < 0.001) and 0.47 _ 0.17 and 0.44 _ 0.25 mg/L after one week (p = 0.64). Baseline samples were not available that soon after birth. Conclusion: A single high dose of intravenous iron isomaltoside for postpartum haemorrhage led to a transient increase in the iron concentration in breast milk three days after treatment compared with oral iron. The difference disappeared one week after treatment, and mean iron concentrations were within the normal range in all samples.